Maternal breastfeeding and labor inclusión - Ponciano Queiroz Araújo, Rosineide; Birnenbaum, Silvia Judith (Southern perspective / Perspectiva austral, 2024)
Introduction: breast milk is the natural and optimal food for the newborn in the first 6 months. Returning to work is one of the periods with the highest risk of discontinuing exclusive breastfeeding, leading mothers to adopt supplementation with milk formulas or even interrupt breastfeeding.Objective: the objective of this study is to identify the facilitators and barriers of mothers in returning to work.Material and method: it is a qualitativequantitative descriptive cross-sectional study. A survey was carried out using a form, made up of 15 closed and open questions. Results: of the 86 interviewed, 98 % continued breastfeeding, at the time of the interview 27 % were receiving breastfeeding, among those who finished, 53,4 % sustained breastfeeding for more than 6 months. The length of leave was mostly between 21 and 45 days, presence of a lactation room (28,5 %), refrigerator for milk storage (57,1 %), breast pump (17,8 %). %), chairs and support tables (46,5 %). Work spaces do not consider the needs to support breastfeeding (68 %). Conclusion: strategies aimed at improving public policies to promote, protect and support breastfeeding for working women, taking into account the numerous benefits it entails for the infant, the mother, and society as a whole